Pericyclic reactions : a mechanistic and problem solving approach - Kumar, Sunil; Kumar, Vinod; Singh, S. P. (Elsevier Academic Press, 2016)
Pericyclic Reactions: A Mechanistic and Problem-Solving Approach provides complete and systematic coverage of pericyclic reactions for researchers and graduate students in organic chemistry and pharmacy programs. Drawing from their cumulative years of teaching in the area, the authors use a clear, problem-solving approach, supplemented with colorful figures and illustrative examples. Written in an accessible and engaging manner, this book covers electrocyclic reactions, sigmatropic reactions, cycloaddition reactions, 1,3-dipolar reactions, group transfer, and ene reactions. It offers an in-depth study of the basic principles of these topics, and devotes equal time to problems and their solutions to further explore those principles and aid reader understanding. Additional practice problems are provided for further study and course use.